A Systematic Review of Prevalence and Predictors of Chronic Kidney Disease in Patients Type 2 Diabetic - Wijayanti, Eka; Lindawati (The Indonesian Journal of General Medicine, 2024)
Background: Chronic kidney disease (CKD) is a progressive loss in renal function over a period of three months or years. Kidneys can get damaged from a physical injury or a disease like diabetes mellitus (DM) or high blood pressure. Once kidneys are damaged, they cannot filter blood or perform other activities. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Ten publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: CKD as a result of type 2 diabetes mellitus has been the main contributor to the increasing burden of CKD over the past several decades. We suggest a more pragmatic approach focusing on early diagnosis, primary care and adequate follow up to reduce mortality and the long‐term burden in low‐to‐middle Sociodemographic Index regions.